Price, service quality, customer trust and safety influence towards customer satisfaction on online transportation - Fong Shi Kanga; Abdul Kamal Char; Geoffrey Harvey Tanakinjal; Bonaventure Boniface; Alesia Sigang Gukang; Liew Anak Lubang (Penerbit UMS, 2023)
This study intends to fill a vacuum in prior research by investigating the effect of pricing, service quality, customer trust, and safety on consumer satisfaction in online transportation. The data was obtained using a Google form and the hypotheses were tested using the Statistical Package for the Social Sciences (SPSS) version 26. According to the findings, price has a big impact on customer satisfaction when it comes to online transportation. This study's findings differ with the previous study's findings, which revealed that pricing has an insignificant effect on consumer satisfaction. The findings also demonstrate that the quality of service has a major impact on consumer satisfaction in online transportation. The findings also reveal that safety has a big impact on customer satisfaction when it comes to online transportation. The limitation of this study is that it only has four independent variables, which are pricing, service quality, customer trust, and safety, and the respondents are limited to 200. Future research can include more factors that influence consumer satisfaction with online transportation, and the number of respondents can be increased, allowing future researchers to obtain different conclusions from this study.